Biomechanical and neuromuscular correlates of DaeDo output during successful dominant- and non-dominant-leg taekwondo side kicks: a repeated-measures study - Yijun Liu; Mengyao Jia (BMC Sports Science, Medicine and Rehabilitation, 2026)
Abstract Objective This study aimed to compare temporal, kinematic, kinetic, and support-side neuromuscular characteristics between dominant- and non-dominant-leg Taekwondo side kicks and to examine their associations with DaeDo output during successful scoring trials. Methods Twelve high-level male Taekwondo athletes, all right-leg dominant, performed side kicks with both legs. Three-dimensional kinematics, force-platform data, support-side surface electromyography (EMG), and DaeDo output were recorded simultaneously. Between-condition differences were examined using paired analyses. Trial-level biomechanical Spearman coefficients were reported descriptively, whereas repeated-measures associations with DaeDo output were examined using linear mixed-effects models. Benjamini–Hochberg false discovery rate (FDR) correction was applied to multiple EMG comparisons. Results DaeDo output did not differ between the dominant- and non-dominant-leg conditions (47.29 ± 6.65 vs. 47.97 ± 5.49, p = 0.501). The dominant-leg condition showed shorter preparation time and higher peak foot velocities in the X and Z directions, peak resultant foot velocity, and peak hip flexion angular velocity. After FDR correction, normalized RMS and iEMG of the tensor fasciae latae during the execution–impact phase were higher in the dominant-leg condition. No condition-specific EMG–DaeDo associations or leg condition × EMG interactions remained significant after FDR correction. In the multivariable mixed-effects model, preparation time was associated with DaeDo output (β = −40.888, p = 0.034), whereas leg condition, peak resultant foot velocity, support-leg anterior–posterior impulse, and the tested biomechanical interaction terms were not significant. Conclusion Successful dominant- and non-dominant-leg side kicks produced comparable DaeDo output despite differences in temporal, kinematic, and support-side EMG characteristics. Preparation time showed the most consistent association with DaeDo output, whereas the present analyses did not support condition-dependent biomechanical or neuromuscular associations with electronic scoring output.